2022
DOI: 10.1007/s11120-022-00935-6
|View full text |Cite
|
Sign up to set email alerts
|

A perspective on the major light-harvesting complex dynamics under the effect of pH, salts, and the photoprotective PsbS protein

Abstract: The photosynthetic apparatus is a highly modular assembly of large pigment-binding proteins. Complexes called antennae can capture the sunlight and direct it from the periphery of two Photosystems (I, II) to the core reaction centers, where it is converted into chemical energy. The apparatus must cope with the natural light fluctuations that can become detrimental to the viability of the photosynthetic organism. Here we present an atomic scale view of the photoprotective mechanism that is activated on this lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 128 publications
0
6
0
Order By: Relevance
“…Nevertheless, questions about how the dynamics of the thylakoid membrane, the lipids therein, and the PsbS protein itself control light harvesting and qE in LHCII remain pressing. Alongside reversible clustering of LHCII in the qE state, light-induced thylakoid membrane thinning has been observed not to correlate with ΔpH as previously proposed, but with qE itself. We had hypothesized that membrane thinning and lipid rearrangements could provide the driving force required to induce and reverse qE-associated LHCII clustering though a hydrophobic mismatch between the proteinaceous and lipid phases of the thylakoid membrane. , Hydrophobic mismatch is a ubiquitous regulatory mechanism in biological membranes . Indeed, in other systems, membrane bilayer thickness has been shown to be a key modulator of membrane protein function and organization .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Nevertheless, questions about how the dynamics of the thylakoid membrane, the lipids therein, and the PsbS protein itself control light harvesting and qE in LHCII remain pressing. Alongside reversible clustering of LHCII in the qE state, light-induced thylakoid membrane thinning has been observed not to correlate with ΔpH as previously proposed, but with qE itself. We had hypothesized that membrane thinning and lipid rearrangements could provide the driving force required to induce and reverse qE-associated LHCII clustering though a hydrophobic mismatch between the proteinaceous and lipid phases of the thylakoid membrane. , Hydrophobic mismatch is a ubiquitous regulatory mechanism in biological membranes . Indeed, in other systems, membrane bilayer thickness has been shown to be a key modulator of membrane protein function and organization .…”
Section: Introductionmentioning
confidence: 88%
“…7−9 We had hypothesized that membrane thinning and lipid rearrangements could provide the driving force required to induce and reverse qE-associated LHCII clustering though a hydrophobic mismatch between the proteinaceous and lipid phases of the thylakoid membrane. 2,10 Hydrophobic mismatch is a ubiquitous regulatory mechanism in biological membranes. 11 Indeed, in other systems, membrane bilayer thickness has been shown to be a key modulator of membrane protein function and organization.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Because H2 is connected through loop regions to both of these transmembrane helices, that could allow the spontaneous movement of H2 when the atomistic resolution is restored. It is worth noting that both the new open arrangement of TM3 and TM4 and the motion of H2 in PsbS appears similar to the conformational change of the LHCII minor antenna CP29, where a lumenal “open” conformation obtained through an enhanced sampling approach exhibits a larger interhelical angle between TM helices A and B (corresponding to TM3/TM4) and more lumen-oriented conformation of helix D (corresponding to H2) …”
mentioning
confidence: 87%
“…31,35,36 In the case of higher plants, it is known that the qE activity relies on the aggregation of LHCII, which is triggered by transmembrane ΔpH and regulated by Zea and PsbS inductors. 37,38 As for the green alga B. corticulans, whose LHCII lacks the xanthophyll-cycle pigments Zea and violaxanthin (Vio), 31 it had been shown that the NPQ activity is independent of ΔpH, Zea, and PsbS and that the chloroplast and algal tuft exhibit prolonged NPQ and preferential accumulation of Spx. 35 To date, the mechanistic details of B. corticulans photoprotection remain largely unexplored, e.g., the molecular mechanism of excessive excitation dissipation and even the role of B-LHCII aggregation are awaiting in-depth studies.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, to cope with the drastically changing light environment of the intertidal zone, B. corticulans must own robust photoprotection mechanisms. ,, In the case of higher plants, it is known that the qE activity relies on the aggregation of LHCII, which is triggered by transmembrane ΔpH and regulated by Zea and PsbS inductors. , As for the green alga B. corticulans, whose LHCII lacks the xanthophyll-cycle pigments Zea and violaxanthin (Vio), it had been shown that the NPQ activity is independent of ΔpH, Zea, and PsbS and that the chloroplast and algal tuft exhibit prolonged NPQ and preferential accumulation of Spx .…”
Section: Introductionmentioning
confidence: 99%